Magnetic resonance cholangiopancreatography in clinical practice - N. V. Tumanskaya; A. V. Klymenko; T. M. Kichangina; N. A. Yareshko; I. P. Dzhos (Zaporozhye State Medical University, 2017)
The review of the literature analyzes the current role of magnetic resonance imaging (MRI) in diagnosing the pathology of intra- and extrahepatic bile ducts. The methodology of the study, the main types of magnetic resonance cholangiopancreatography, the features of their conduct are described. The main indications for the use of the method are given, the possibilities of MRI-cholangiography and the factors influencing the research and interpretation of the obtained data are estimated.